Plasmonics for hydrogen energy - Tanabe, Katsuaki (Springer, 2022)
This book provides an overview of the fundamentals of plasmonic field enhancement phenomena and the recent advancements in the field of hydrogen energy technologies that utilize plasmonics for their performance enhancement. Hydrogen energy is currently a representative clean energy without polluting or greenhouse emission in its use. However, industrial production of hydrogen molecules, or other usable hydrogen-containing molecules, is required for the use of hydrogen energy. It is also important to produce hydrogen in clean, renewable manners, to contribute to the solution of the environmental problems, such as atmospheric pollution and global warming, and of the depletion of energy resources. For the widespread use of hydrogen energy, technical developments particularly for hydrogen production and storage are highly sought after. Free electrons in metals, particularly around metal surfaces or interfaces with dielectric materials, exhibit a strong interaction with electromagnetic fields or light in the form of collective oscillation, named surface plasmons. The electromagnetic field intensity around subwavelength-size metal particles can be highly localized due to the coupling between the incident photons and collective oscillation of free electrons at the metal surface, resulting in focusing of electromagnetic energy density, or namely local field enhancement.
Keywords: Plasmonics.; Hydrogen as fuel.; elektronické knihy; electronic books